Mixing methods to explore appearance in dementia care. (May 2013) - Ward, Richard; Campbell, Sarah
This paper considers approaches to investigating appearance and the work invested in maintaining it within dementia care. Our focus is upon methodological and methods-related issues associated with the challenge of generating knowledge of the embodied worlds of people with dementia. We begin with a brief overview of the literature on appearance and dementia, and consider what it teaches us about the nature of appearance and ways of understanding it. We describe and discuss the mixing of methods for an on-going investigation into hairdressing in dementia care: The Hair and Care project. Based upon the experience of research in care-based hair salons, we argue for a creative use of methods in dementia studies as an avenue to better engaging with the embodied experiences of people with dementia and, as a result, understanding how people use their bodies and senses to create meaningful worlds.